2012
DOI: 10.1111/j.1524-4725.2011.02192.x
|View full text |Cite|
|
Sign up to set email alerts
|

Autologous Fibroblast Culture in the Repair of Aging Skin

Abstract: Injection of skin fibroblasts cultivated in medium supplemented with human serum is a viable technique and provokes no side effects. Four injections given at 15-day intervals containing a total of 6.4 × 10(6) fibroblasts/mL resulted in significant improvement in periorbital skin flaccidity. Further studies should be conducted with larger sample sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In clinical aesthetic medicine, epidermal or intradermal injection of hyaluronic acid is performed to obtain glossy and healthy skin (microinjections of hyaluronic acid, vitamins, minerals, and amino acids into the superficial layer of the skin) [15]. Other techniques, such as implanting activated fibroblasts in the skin, are also known to revive the skin to be glossy and healthy (intradermal injection of cultivated skin fibroblasts into wrinkles) [16-18]. However, these therapies are associated with a high cost and may provoke adverse events, including misplacement, allergy, nodules, necrosis, abscesses, and rejection.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical aesthetic medicine, epidermal or intradermal injection of hyaluronic acid is performed to obtain glossy and healthy skin (microinjections of hyaluronic acid, vitamins, minerals, and amino acids into the superficial layer of the skin) [15]. Other techniques, such as implanting activated fibroblasts in the skin, are also known to revive the skin to be glossy and healthy (intradermal injection of cultivated skin fibroblasts into wrinkles) [16-18]. However, these therapies are associated with a high cost and may provoke adverse events, including misplacement, allergy, nodules, necrosis, abscesses, and rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Milk treatment can soothe irritated skin, can hydrate dry skin, and can replenish lost nutrients. It has been reported that skin wrinkles were treated with implanted autologous fibroblasts, which resulted in a significant improvement in periorbital skin flaccidity [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond this however, there has been much interest in cultured stem cells and autologous cells for their use in regenerative medicine 96 . There have multiple studies demonstrating that autologous cultured skin fibroblast therapy can be used to correct rhytids and skin flaccidity 74,75 . Additional studies have even demonstrated the ability to correct skin discoloration seen with diseases such as vitiligo 76 .…”
Section: In Vitro Models a Cell Culturementioning
confidence: 99%
“…80 There have been multiple studies demonstrating that autologous cultured skin fibroblast therapy can be used to correct rhytids and skin flaccidity. 81,82 Additional studies have even demonstrated the ability to correct skin discoloration seen with diseases such as vitiligo. 83 Injected adipose-derived stem cells have been shown to increase collagen synthesis in hairless mice, improve dermal thickness, and promote angiogenesis.…”
Section: In Vitro Models Cell Culturementioning
confidence: 99%